Analysis of The Influence of Leadership Style on Job Achievement at Madani Shariah Medan Hotel with Motivation as Intervening Variabl - Hubbul Wathan; Muhammad Zuardi; Rehulina Bangun (International ABEC, 2021)
Hotel Madani Syariah is one of the hotels that uses management principles based on sharia. In the management aspect, the organization has the principle of mutual benefit between the leader and the led. This study aims to determine the performance of employees at the Madani Syariah Hotel Medan. Leaders have the right to be obeyed as long as they do not violate the Shari'a, as well as employees have the right to be prospered with compensation according to their field of work. Employees as important assets in the success of the company must be maintained and maintained like company assets. Human resources are the main factor that is very important for an organization. Human resources cannot be separated from the process of how to achieve organizational goals and human resources can support the achievement of these goals cannot be separated from how the leadership style is applied to create employee motivation and produce good work performance. The conclusion in this research are the leadership style applied by the manager of Hotel Madani Syariah Medan tends to be a leadership style called the inviting leader as well, with high motivation and achievement of employees. As for the advice, the direct supervisor of Hotel Madani Syariah Medan should pay more attention to the feelings of subordinates in actions and actions.